Combined shape and non-shape sensitivity for optimal design of metal forming operations - Antunez, Horacio J.; Kowalczyk, Maciej (Computer Assisted Methods in Engineering and Science; Vol 11 No 1 (2004), 2023)
Shape and non-shape optimization is carried out for metal forming processes. This means a unified treatment of both shape parameters and other process parameters which are assumed to be design variables. An optimization algorithm makes use of the results of the analysis problem and of the sensitivity parameters obtained as a byproduct of the basic solution, in the context of the direct differentiation method. The shape sensitivity stage is formulated within the domain parametrization approach. Two alternative mappings are proposed to obtain the required derivatives with respect to the shape parameters. The behaviour of different functionals considered and the effect of the boundary conditions on the optimal design are discussed.